Impacts of wildfire on soil characteristics in subtropical Chir Pine forests of Murree, Pakistan - Arif Hussain; Muhammad Irfan Ashraf; Sajjad Hussain; Muhammad Atif; Beenish Akram Khan (International Journal of Applied and Experimental Biology)
Wildfires are a natural component of forest ecosystem. These fires are a major cause of significant perturbations in the forest habitat due to temperature extremes and drought conditions particularly in summer. Wildfires occur frequently during summer in the subtropical Chir pine forests of Murree, Pakistan. These fires influence soil characteristics as well as tree-species growth and survival. The present study was thus conducted to investigate soil characteristics of wildfire-affected and non-affected areas. Four sites were selected based on wildfire incidents in the study area. Soil samples were collected from the fire-affected and adjacent non-affected areas. The collected soil samples were analyzed for physical and chemical characteristics using appropriate methods. The study showed that bulk density, moisture content, electrical conductivity, and soil nitrogen and soil carbon content declined in the burnt soil. However, soil pH, and phosphorus and potassium contents were higher in the burnt soils than those in the non-burnt soils. Generally, low intensity forest fire (surface fire) is an important component of forest ecosystem and it enhances natural regeneration as well as soil fertility. It is suggested that government forest departments should take into account burn severity while developing hazard reduction and restoration strategies of wildfire affected areas.